(untitled) (World Bulletin of Social Sciences, 2021)
Since the beginning of the new century, it is possible to sum up certain results of the heated debate about the rational method of teaching foreign languages (FL) that took place over the past century, to establish the reasons for the evolution or involution of methods in different learning conditions, to identify trends in changing methods in the foreseeable future. It was in the XX century, countless new methods have emerged, claiming and claiming the "best" learning outcomes.